A case report of hypertensive bleed presenting with pathological laughter: Focus on neurobiological correlates and pharmacological management - Sujita Kumar Kar (Journal of Geriatric Mental Health, 2015)
Pathological laughter and crying are episodes of either laughter or crying, which is intense and uncontrollable, usually lasting for brief periods and occurring in paroxysms. In the literature, pathological laughing and crying, emotionalism, pseudo-bulbar affect are synonymously used. Favorable evidences exist with regard to the use of antidepressants, mood stabilizers, and anti-glutaminergic agents for the management of pathological laughter and crying. In this case report, we highlight the clinical presentation of hypertensive bleed in the form of pathological laughter and its management with selective serotonin reuptake inhibitor - sertraline along with literature review regarding its neurobiological basis and pharmacological management.